Why do lactic acid bacteria thrive in chain elongation microbiomes? - Ulčar, Barbara; Regueira, Alberte; Podojsteršek, Maja; Boon, Nico; Ganigué, Ramon (Frontiers in Bioengineering and Biotechnology, 2024)
Efficient waste management is necessary to transition towards a more sustainable society. An emerging trend is to use mixed culture biotechnology to produce chemicals from organic waste. Insights into the metabolic interactions between community members and their growth characterization are needed to mediate knowledge-driven bioprocess development and optimization. Here, a granular sludge bioprocess for the production of caproic acid through sugar-based chain elongation metabolism was established. Lactic acid and chain-elongating bacteria were identified as the two main functional guilds in the granular community. The growth features of the main community representatives (isolate Limosilactobacillus musocae G03 for lactic acid bacteria and type strain Caproiciproducens lactatifermentans for chain-elongating bacteria) were characterized. The measured growth rates of lactic acid bacteria (0.051 ± 0.005 h -1 ) were two times higher than those of chain-elongating bacteria (0.026 ± 0.004 h -1 ), while the biomass yields of lactic acid bacteria (0.120 ± 0.005 g biomass/g glucose) were two times lower than that of chain-elongating bacteria (0.239 ± 0.007 g biomass/g glucose). This points towards differential growth strategies, with lactic acid bacteria resembling that of a r-strategist and chain-elongating bacteria resembling that of a K-strategist. Furthermore, the half-saturation constant of glucose for L. mucosae was determined to be 0.35 ± 0.05 g/L of glucose. A linear trend of caproic acid inhibition on the growth of L. mucosae was observed, and the growth inhibitory caproic acid concentration was predicted to be 13.6 ± 0.5 g/L, which is the highest reported so far. The preadjustment of L. mucosae to 4 g/L of caproic acid did not improve the overall resistance to it, but did restore the growth rates at low caproic acid concentrations (1 -4 g/L) to the baseline values (i.e. growth rate at 0 g/L of caproic acid). Here, insights into the growth of two main functional guilds of sugarbased chain elongation systems are provided which allows for a better understanding of their interactions and promotes future bioprocess design and optimization.